Twenty-first century biopolitics and political realism - Koljević Grifit, Bogdana (Sociološki pregled, 2023)
In this paper we will consider the concept of biopolitics as neoliberalism, i.e., the reflections of the fundamentals of Foucault’s theory and its structurally post-political character. The primary goal is to understand how this specific “regime of truth” turns out to be the foundation of the twenty-first century Realpolitik, from which Western government techniques derive. Biopolitics relevantly emerges as a process of fragmentation and dissolution of political sovereignty and subjectivity, and, as such, it is exacted through various postmodern and neoliberal forms. They defy a substantial portion of philosophical and legal traditions through politicization of life, the theory, and practices of biopolitics. In the second part of the paper – along with an overview of the contemporary phenomena of biopolitics – we articulate Foucault’s position of political realism as a potential answer to political-philosophical challenges on a global scale.
Keywords: biopolitics; neoliberalism; subjectivity; sovereignty; political realism